2011
DOI: 10.1007/dcr.0b013e318202f922
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Stimulation: A Novel Treatment of Chronic Anal Fissure

Abstract: Sacral nerve stimulation offers an effective alternative treatment option for chronic anal fissure in patients who chose not to pursue more invasive surgical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Sacral nerve stimulation (SNS) has been used since the 1980s as a treatment for dysfunction of pelvic and abdominal organs and pelvic pain. Sacral nerve stimulation has been recently shown to be an effective treatment modality for CAF as reported in a study which included five patients suffering CAF [10]. Complications related to SNS therapy include patients discomfort at the subcutaneous tunnel in which the electrodes run [19] and superficial wound infection which occurs in 3%e17% of patients [19,20].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Sacral nerve stimulation (SNS) has been used since the 1980s as a treatment for dysfunction of pelvic and abdominal organs and pelvic pain. Sacral nerve stimulation has been recently shown to be an effective treatment modality for CAF as reported in a study which included five patients suffering CAF [10]. Complications related to SNS therapy include patients discomfort at the subcutaneous tunnel in which the electrodes run [19] and superficial wound infection which occurs in 3%e17% of patients [19,20].…”
Section: Discussionmentioning
confidence: 97%
“…Recurrence was observed in 11 (40.7%) of 27 patients who reported clinical improvement. Yakovlev et al [10] performed a pilot study on five patients with CAF who underwent SNS and reported that all study participants showed improvement with no recurrence of anal fissure 1 year after treatment. Altunrende et al [22], applied transcutaneous electrical posterior tibial nerve stimulation for ten patients with CAF and reported improvement of symptoms in all patients by the tenth session.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…because the relief of the spasm has been associated with relief of pain and healing of the fissure [3].…”
mentioning
confidence: 99%